2021
DOI: 10.34172/ijhpm.2021.116
|View full text |Cite
|
Sign up to set email alerts
|

Health Coverage and Financial Protection in Uganda: A Political Economy Perspective

Abstract: Background: As countries health financing policies supporting progress towards Universal Health Coverage (UHC), an analysis of these policies is particularly relevant in Low and Middle-Income Countries (LMICs). In 2001, the government of Uganda abolished user-fees to improve accessibility to health services for the population. However, after almost 20 years, the incidence of catastrophic health expenditures is still very high, and the health financing system does not provide a pooled prepayment scheme at natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…Studies have also shown the influence of market economy ideologies. The neoliberal agenda of the 1980s–1990s had adverse effects in Ghana,36 Zimbabwe24 and Uganda 78. In South Africa, the SHI lost momentum when the country adopted the neoliberal-laden Growth, Employment and Redistribution (GEAR) 40 which favoured efficiencies and control of public sector expenditure 38 39.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown the influence of market economy ideologies. The neoliberal agenda of the 1980s–1990s had adverse effects in Ghana,36 Zimbabwe24 and Uganda 78. In South Africa, the SHI lost momentum when the country adopted the neoliberal-laden Growth, Employment and Redistribution (GEAR) 40 which favoured efficiencies and control of public sector expenditure 38 39.…”
Section: Methodsmentioning
confidence: 99%
“…The desire to win or stay in government plays a major role in shaping health reforms, particularly if the opposition political parties raise reforms on the campaign plank. However, reforms that are primary driven by electoral motives are often populistic, hurried and technically weak 78 as in the case of user fee removal 132 and community health initiatives. 122 This study also found that political ideologies have a profound effect on policy reforms.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…15 In addition, the "free healthcare" policy was perceived as inconsistent with the introduction of premiums under NHIS-counteracting policy adoption. 4 In conclusion, this paper raises key considerations to practically change the 'rules of the game' of how PEA is deployed as both a practical and theoretical tool. First, disaggregating while carefully linking the PEA concepts increases their viability as analytical tools for researchers and policymakers to think and work politically.…”
Section: Centrality Of Powermentioning
confidence: 98%
“…2 However, defining politics and related concepts is not straightforward. 3 Nannini et al, 4 in their paper on health financing reforms in Uganda, underscore the relevance of the political economy (PE) lens in understanding the dynamics of advancing universal health coverage aspirations. The authors applied a conceptual framework with several domains, including stakeholders and institutions, politics (interests and ideologies), policy implementation and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Yet once attaining power, the ideology changed towards the supremacy of the market forces, without being accountable electorally. 1 At present there is a stark imbalance between the concentrated political power of the private sector in healthcare, versus the fragmented and diffuse social-forces of communities, advocacy groups, and people who would benefit from UHC. Government officials have, perhaps perversely, tended to rely on external donors for both funding and leadership, without the necessary accountability and commitment for UHC.…”
Section: Identifying and Creating Political Opportunities: The 2030 A...mentioning
confidence: 99%